2004
DOI: 10.1165/rcmb.2003-0338rc
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Possible Role of a Novel Gene, DPCD, in Primary Ciliary Dyskinesia

Abstract: Primary ciliary dyskinesia (PCD) is an autosomal recessive disease caused by mutations that affect the proper function of cilia. Recently, deletion of DNA polymerase lambda (Poll) in mice produced a phenotype characteristic of PCD (Kobayashi et al., 2002, Mol. Cell. Biol. 22:2769-2776). Because it is unclear how a mutation in a DNA polymerase would result in a specific defect in axonemes, the targeting construct was examined further. Analysis of the genomic region surrounding the Poll gene revealed an uncharac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 22 publications
2
48
0
1
Order By: Relevance
“…All the acetyl proteins related to sperm motility highlighted by the previous study (31) except DPCD were identified in both studies (Table II), indicating that a minor difference between capacitated and uncapacitated human sperm in terms of protein types might exist, although capacitated sperm were apparently different from uncapacitated sperm in motility. However, because DPCD appeared to be a novel candidate for primary ciliary dyskinesia (38) and Dpcd/ Poll(Ϫ/Ϫ) mice had deficient ciliary motility (39), DPCD acetylation might be a key event in the process of sperm capacitation and ciliary motility that is worth further investigation in the future. Besides, of the four acetyl proteins that might be involved in fusion of sperm-egg plasma (31), only ROPN1B was identified in the present study (Table II), which implied that there are dramatic changes after capacitation in terms of lysine acetylation of these proteins.…”
Section: Table I Synthesized Peptides Peptide Libraries and Peptide-mentioning
confidence: 99%
“…All the acetyl proteins related to sperm motility highlighted by the previous study (31) except DPCD were identified in both studies (Table II), indicating that a minor difference between capacitated and uncapacitated human sperm in terms of protein types might exist, although capacitated sperm were apparently different from uncapacitated sperm in motility. However, because DPCD appeared to be a novel candidate for primary ciliary dyskinesia (38) and Dpcd/ Poll(Ϫ/Ϫ) mice had deficient ciliary motility (39), DPCD acetylation might be a key event in the process of sperm capacitation and ciliary motility that is worth further investigation in the future. Besides, of the four acetyl proteins that might be involved in fusion of sperm-egg plasma (31), only ROPN1B was identified in the present study (Table II), which implied that there are dramatic changes after capacitation in terms of lysine acetylation of these proteins.…”
Section: Table I Synthesized Peptides Peptide Libraries and Peptide-mentioning
confidence: 99%
“…Deletion of RP11-529I10.4/DPCD in mice results in a phenotype similar to primary ciliary dyskinesia (PCD) (Zariwala et al 2004). PCD is a genetic disorder characterized by a defect in axonemal structure resulting in hindrance of normal ciliated and flagellar cells, most notably of the respiratory tract.…”
Section: Znhit2 and Rp11-529i104mentioning
confidence: 99%
“…Nasal nitric oxide (NO) was measured as described previously (3,26). Blood or buccal cells were obtained from the proband (and relatives when possible) for DNA extraction (3,26,38). Genomic DNA was obtained from 106 patients with PCD (90 families) from diverse geographical locations, including Germany (n ϭ 28), France (n ϭ 23), United Kingdom (n ϭ 18), Australia (n ϭ 11), Italy (n ϭ 6), Israel (n ϭ 2), Pakistan (n ϭ 1), and the United States (n ϭ 1).…”
Section: Subjects: Clinical Evaluationmentioning
confidence: 99%